The cycles of impermanent alterity in Nazaré - Silva, Cidália Ferreira (2018)
What happens when a small city expands from 15,000 to 100,000 inhabitants in the summertime? How do temporary inhabitants of Nazaré (Portugal) change the rhythms of its everyday life? How does largescale tourism change their supporting economic activities or even replace activities such as fishing? Is this seemingly rigid urban fabric elastic enough to expand and adapt to these exponential “others”? The “impermanent alterity” explains the result of the relationship established between land and water, between the “I” and the “other” that come to Nazaré to step onto the warm sand during the summer days. There is a visible cycle of summer-winter change, which the network of lived time interconnections can be found in simple things like the gray pavement line organizing uses, as a device that adapts matter to the cycles of change. Time is the operator of this “impermanent alterity,” and the residents and outsiders alike make it visible.